Evaluadores del Volumen 36(1) - ., Runa (RUNA, archivo para las ciencias del hombre, 2015)
Evaluadores Nacionales • Adelaida Colángelo – UNLP, La Plata • Alejandro Isla – FLACSO • Ana Guglielmucci – CONICET-UBA • Axel Lazzari – UNSaM • Beatriz Goldwaser – UNLu, Luján • Carolina Duek – I.I.G.G., UBA • María Carolina Feito – Facultad de Agronomía, UBA • Eva Muzzoppapa – UNRN, Río Negro • Gisella Cassiodoro – INAPL, CONICET • Hernán Palermo – CEIL / CONICET • Julieta Gómez Otero – CENPAT / CONICET / UNPSJ, Pto. Madryn, Chubut • Maria Soledad Gheggi – CRILAR / CONICET, Anillaco, La Rioja • Patricia Arenas – UNT / UNSE, Tucumán – Santiago del Estero Evaluadores Extanjeros • Gonzalo Figueiro – Universidad de la República del Uruguay, Uruguay • Luciana Hartman – Universidade de Brasília, Brasil • Marta Cioccari – Universidade Federal do Rio de Janeiro, Brasil